Sensoric Quality of Kemantan Fruit Syrup With The Addition of Bay Leaf - duda, hilarius jago; Syafruddin, Didin; Wahyuni, F. Rahayu Esti; Bustami, Yakobus (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Kemantan (Mangifera torquenda Kosterm) is a local fruit found in West Kalimantan which is rarely studied and is well known to many people. Kemantan is a genus with mango. Mango is one of the leading tropical fruits favored by people in the world. Mango is also famous for its content of multi vitamin, antioxidants, and many other nutritional content. Bay leaves (Eugenia polyantha) contain essential oils (citral, eugenol), tannins and flavonoids. Unfortunately, so far these two plants have only been consumed traditionally so they are boring and the rest is thrown away, therefore researchers want to use these plants to make fruit syrup. The research method was an experiment with a completely randomized design consisting of 1 treatment and 5 levels of bay leaf addition denoted by the letter (S). The materials used in this study for the manufacture of the product consisted of kemantan fruit, bay leaves, granulated sugar, CMC, and other. The steps: first, making bay leaf extract, second, making kemantan fruit syrup. Organoleptic test to provide an assessment of color, aroma, taste, texture, thickness, preference and overall with the rating format 5-1. Data analysis was carried out using the ANOVA method and the results were significantly different followed by the LSD test. The results showed that the best treatment for kemantan syrup products was S0 for color and aroma assessment. While the treatment for taste, thickness, texture, preference and overall assessment was S1. Kemantan syrup with the addition of bay leaves has a significant effect on texture parameters, very significant effect on color, taste, thickness, preference and overall and no significant effect on aroma